PREGNANCY OUTCOMES IN SINGLE FROZEN BLASTOCYST CYCLES AFTER THAWING AND CULTURING FOR AN ADDITIONAL 16-20 HOURS (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate whether prolonged post-thaw culture duration (16-20 hours) affects the development of embryos  and pregnancy outcomes in single frozen blastocyst transfer cycles.Methods: This retrospective study included 263 single frozen-thawed day 5 blastocyst transfer cycles between January 2021 and December 2023 at the Department of Assisted ReproductiveTechnology & Andrology, Hanoi Obstetrics and Gynecology Hospital. Blastocyst had blastocoel expansion stage from 1 to 3 before freezing and cultured 16-20 hours after thawing until embryo transfers. The main outcomes were the blastocyst morphology parameters-expansion, inner cell mass (ICM), trophectoderm grade (TE) and the pregnancy rate, implantation rate.Results: After 16-20 hours of culture, embryos with blastocoel expansion from stage 1 to stage 3 showed development in both the degree of blastocoel expansion and the quality of the ICM and TE. Stage 1 embryos could progress to stages 2-4 (69.7%), stage 2 embryos developed to stages 3-5 (90%), and stage 3 embryos progressed to stages 4-6 (67.5%). The ICM and TE could be evaluated more clearly. The pregnancy rate was 66.9%, and the implantation rate was 57.5%. Embryos developing to stages 4 and 5 had the best outcomes.Conclusions: A 16-20 hour post-thaw culture can be applied to embryos with blastocoel expansion stages from 1 to 3 to enhance embryo development, allow better assessment of embryo quality, and improve the prediction of embryo transfer outcomes.
Keywords: Overnight culture, pregnancy rate, implantation rate, post-thaw culture duration.